Good or bad news first? The effect of feedback order on motivation and performance - Lavinia Kinne (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2023)
How to give feedback in learning environments is a widely discussed topic. I design a field experiment to understand whether the ordering of feedback elements matters for motivation and performance. In random order, university students get one positive and one negative feedback element on their performance in exam practice questions. Students who first receive positive feedback are more motivated to study for the exam compared to those receiving negative feedback first. This effect is driven by a drop in motivation after negative feedback when receiving it first, but not when receiving it second. Furthermore, students adjust their study content to the feedback topics. I find no significant effects of feedback ordering on exam performance overall, but students who first receive the positive feedback perform better if their negative-feedback topic is covered in the exam.
Keywords: D83; I20; I23; 330; Education; feedback; motivation; performance